The prevalence of elongated styloid process in the population of Barcelona: a cross-sectional study & review of literature - Hassan Assiri Ahmed; Albert Estrugo-Devesa; Xavier Roselló Llabrés; Sonia Egido-Moreno; José López-López (BMC Oral Health, 2023)
Abstract Background Styloid process (SP) is a cylindrical bony projection that originates from the inferior part of the petrous temporal bone just anteriorly to the stylomastoid foramen. Several nerves, muscles, and ligaments are related closely to the (SP). It is considered elongated when the measurement exceeds 30 mm. The overall prevalence of the styloid process is between 3.3% to 84.4%. The elongation of the styloid process (ESP) is associated with the manifestation of Eagle’s Syndrome (ES) which is characterized by various types of pain in the head and neck region such as headache, tinnitus, otalgia, and trigeminal neuralgia. Eagle’s syndrome occurs in 4–10.3% of individuals with an elongated styloid process (ESP). The objective of the study is to determine the prevalence of (ESP) in the patients who were treated in the Dental Hospital University of Barcelona (HOUB), to review the literature to spot the light on the different demographic data worldwide. Methods The archived panoramic image in the University of Barcelona dental Hospital were consecutively retrieved to investigate the prevalence of (ESP). Of all digital panoramic radiographs (OPG), 400 met the inclusion criteria and were furtherly analyzed. The results are correlated with the participant’s gender, age, and occurrence. Age is subcategorized into three groups. A chi-square test is used to measure the significant differences and the P-value is set at < 0.05 for the level of significance. Results Among the included 400, we found 291 demonstrating (ESP). The prevalence of (ESP) which exceeds 30 mm is 72.75%. It is found that the most common morphological type is type 1 which is regarded as the uninterrupted (ESP) regardless of gender and age group. Concerning the calcification pattern, the most prevalent is the partial calcified (ESP) despite genders and age groups. Conclusion (OPG) is a sufficient tool for the screening of the elongated styloid process. Regarding the prevalence, our results are considered higher than previously reported prevalence in different populations using (OPG) radiography tool. A study on a wider spectrum of the Spanish population is recommended to further investigate the correlation between the elongated styloid process and the occurrence of Eagle’s syndrome.